2020
DOI: 10.1021/acs.jpcc.0c01845
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Luminescence and Photocatalytic Activities of BiVO4 by Eu3+ Ions Incorporation

Abstract: BiVO4 was selected as a model to manipulate the luminescence and photocatalysis by Eu3+ ions incorporation. Eu3+-uniformly doped and surface-localized BiVO4 was prepared by a coprecipitation route and cation exchanges, respectively. The phase-formations, surface characteristics, and band structures were measured. A comparative study of photoenergy conversion activities, that is, photocatalysis and photoluminescence, was conducted. Eu3+-surface-localizing on BiVO4 improves both visible light harvest and photode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Rare earth ion doping can effectively optimize photocatalytic performance by narrowing the band gap, expanding absorption, changing the band position, and promoting carrier separation, while rare earth elements with incomplete occupation of 4F orbital can increase light absorption and separate photogenerated charges. 108 Gu et al 109 used hydrothermal method to replace Bi 3+ with Ce 3+ to prepare BiVO 4 doped with Ce, in which doping of Ce induced the transformation of bismuth vanadate from monoclinic phase to tetragonal phase structure. Bi 3+ ions of Ce 4+ in the substituted lattice produce charged defect states.…”
Section: Performance Improvement Methodsmentioning
confidence: 99%
“…Rare earth ion doping can effectively optimize photocatalytic performance by narrowing the band gap, expanding absorption, changing the band position, and promoting carrier separation, while rare earth elements with incomplete occupation of 4F orbital can increase light absorption and separate photogenerated charges. 108 Gu et al 109 used hydrothermal method to replace Bi 3+ with Ce 3+ to prepare BiVO 4 doped with Ce, in which doping of Ce induced the transformation of bismuth vanadate from monoclinic phase to tetragonal phase structure. Bi 3+ ions of Ce 4+ in the substituted lattice produce charged defect states.…”
Section: Performance Improvement Methodsmentioning
confidence: 99%
“…30 Photoluminescence spectroscopy (PL) was performed using a Hitachi F-4500 fluorescence spectrophotometer, and with the aid of it, the electron hole movement of the samples was measured. 31 The photocurrent ( i – t ) curve and electrochemical impedance spectra (EIS) were obtained using a CHI660E electrochemical workstation from Shanghai Chenhua Instrument Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, lanthanide ions with a unique 4f electron configuration are considered to be efficient dopants to enhance the photocatalytic activity of BiVO 4 . 4 To date, several studies have focused on lanthanide ion-modified monoclinic phase BiVO 4 photocatalysts, such as Ce, La, Gd, Nd and Sm. 5 These findings established the enhancement of photocatalytic activities and revealed that the lanthanide ions were present as oxides on the surface of BiVO 4 .…”
Section: Introductionmentioning
confidence: 99%